Cyber-Religion and the Issue of Religious Authority: How Indonesian Youth Learn Religion through Social Media? - Chair, Badrul Munir; Wawaysadhya; Oktafiani, Tri Utami (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2024)
In recent years, there has been a high increase in social media activity for religious purposes. The abundance of social media activity based on a religious theme excessively emerged, namely online preaching, virtual worship, and a new term called ngaji virtual. This paper uses the phenomenological research method to analyze religious phenomena in social media as a new form of cyberculture, grown excessively during and after the pandemic. Data for this study were collected from 150 respondents who were followers of online religious recitations or lectures on social media platforms, particularly on Facebook, YouTube, and Instagram. This study aims to explain the motives of faith-based social media users, with an additional appraisal of their impact on their daily lives. The results showed numerous motives of faith-based social media users, namely the necessity of information about religion and spiritual enlightenment, and even emphasizing that their worship is valid. Social media as a source of information about religion became more widespread after the pandemic, making social media the primary source for obtaining religious knowledge and growing into a new culture. The emergence of this new cyberculture renders disruption in the religious field, from ethical problems to the problem of obscuring religious authority.